VD_FINDINFO HC / 2011 / 327 vom 1. April 2011 - VD Tribunal cantonal (2011)
AVOCAT, HONORAIRES, DILIGENCE, COMMUNICATION, RETARD, RÉDUCTIONEN GÉNÉRAL, TRANSACTION EXTRAJUDICIAIRE, ENRICHISSEMENT ILLÉGITIME | 23 CO, 24 al. 1 ch. 4 CO, 31 CO, 62 CO, 63 CO, 451 ch. 3 CPC, 452 al. 2 CPC, 465 al. 1 CPC, 405 al. 1 CPC (CH)